PENYULUHAN MANAJEMEN PEMBERIAN PAKAN TERNAK KAMBING PADA MASYARAKAT PENERIMA BANTUAN TERNAK KAMBING DI DESA ALUE DAWAH KECAMATAN BABAH ROT - Susanti, Desi; Triandita, Nanda; Rahmi, Suci; Maryati, Sri; Anggriawin, Mirza; Husin, Hasanuddin; ., Jasmi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Kristen Wira Wacana Sumba, 2022)
One of the keys to success in livestock farming is the provision of appropriate animal feed, especially goat farming. The feed ingredients for goats consist of forage in the form of fresh grass and silage, concentrate, supplementary feed and additional feed. The purpose of this activity is to increase knowledge about the management of goat feed for the recipients of goat livestock assistance from APBG funds in Alue Dawah Village, Babah Rot District, Southwest Aceh Regency. The method used in this service is the extension method, in the form of material exposure and introduction to the types of goat feed and management of feeding according to the life phases of goats, namely the growth, pregnancy and lactation phases. This activity was attended by 38 participants. Counseling is in the form of material presentation and introduction of forage forage, then followed by discussion or question and answer. The participants were able to understand how good goat feed management is and know the right way to cultivate goats.